Basic concepts in biostatistics with step by step in SPSS - Aleng, Nor Azlida; Wan Ahmad, Wan Muhamad Amir; Mohd Ibrahim, Mohamad Shafiq; Ali, Zalila (Penerbit UMT, 2019)
Basic concepts in biostatistics using SPSS emphasizes on an early exposure of basic biostatistics in developing the research skill among the early undergraduate undertaking research project. The special of this book is its integration with the SPSS software and friendly. This is to make sure that the readers can easily understand and design the research according to their research objectives. This book is designed with a very basic and intermediate useful technique which includes parametric and nonparametric test, categorical data analysis and regression techniques. This book also provide a clear step by step approach through screenshot in SPSS that are very important for ensuring the readers in gaining a better understanding for interpreting the results. Through this book, it is hoped that the readers could plan their research by choosing the right selections of the right statistical test. Happy reading.